Probiotics, metabolism and the functional condition of cardio-vascular system - Ye. A. Kashukh; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To characterize possible relation between microbiome and cardio-vascular system structural and functional state. Key points. Along with traditional concepts on the risk factors of atherosclerosis and cardio-vascular diseases development one should take into account data on the new pathogenic mechanisms for these diseases. According to recent studies human gastrointestinal microbiome may increase cardiovascular risk due to bacterial production of proinflammatory proteins that both promote development of atherosclerosis and directly affect the heart and vessels. Probiotics, that are mainly prescribed at gastroenterological diseases, may be applied for correction of cardiovascular risk factors as well. Obtained data demonstrate that intake of certain probiotic strains may be applied as a successful treatment of atherosclerosis, systemic hypertension, metabolic syndrome and heart failure. Conclusion. Microbiome may be involved in development of cardio-vascular diseases and atherosclerosis due to metabolic symbiosis with the host. Probiotics may be applied as preventive medication for correction of metabolic disorders that result in development of cardio-vascular diseases and atherosclerosis.